2014
DOI: 10.1097/bpo.0b013e3182a00890
|View full text |Cite
|
Sign up to set email alerts
|

Results of Single-staged Rotational Osteotomy in a Child With Congenital Proximal Radioulnar Synostosis

Abstract: Level IV--therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 10 publications
3
36
1
9
Order By: Relevance
“…In our series, all patients underwent derotational osteotomy at the synostosis site followed by the plate for rigid internal fixation in case of correction loss, and plaster splint was used for external immobilization, which enabled convenient close observation to monitor edema and peripheral circulation as well as ease of release. There were no increases in the incidence of complications by using plate fixation in our study compared with other fixation methods such as K-wires and/or casts reported by other authors [7, 9, 14, 22].…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In our series, all patients underwent derotational osteotomy at the synostosis site followed by the plate for rigid internal fixation in case of correction loss, and plaster splint was used for external immobilization, which enabled convenient close observation to monitor edema and peripheral circulation as well as ease of release. There were no increases in the incidence of complications by using plate fixation in our study compared with other fixation methods such as K-wires and/or casts reported by other authors [7, 9, 14, 22].…”
Section: Discussioncontrasting
confidence: 53%
“…Currently, derotational osteotomy remains the most commonly performed procedure in patients with CRUS [3, 58], which alters the position of the forearm from hyperpronation to a more functional position to reduce supination limitations and to allow patients to more easily perform activities of daily life. There are many types of osteotomy and fixation methods, including derotational osteotomy at the synostosis site with K-wire fixation [9], one-stage or two-stage double-level derotational osteotomy of the ulna and the radius fixed with plaster casts [7, 10], one- stage double-level derotational osteotomy of the ulna and the radius with K-wire fixation [11, 14], and single osteotomy of the radial diaphysis fixed with plaster casts [8, 15]. The reported complications of the above methods include nerve palsy, compartment syndrome, loss of correction, residual angulation, delayed union, and nonunion.…”
Section: Introductionmentioning
confidence: 99%
“…Derotation osteotomy of the forearm was effective in correcting pronation deformities in young children with congenital radioulnar synostosis 51,52 . Although soft-tissue distraction facilitates centralization for congenital radial longitudinal deficiency, it does not prevent recurrence of deformity 53 .…”
Section: Pediatric and Adult Reconstructionmentioning
confidence: 99%
“…El objetivo del tratamiento quirúrgico es conseguir que los antebrazos adquieran una posición más funcional para la vida del paciente. Se han publicado buenos resultados con la osteotomía desrotacional aislada del radio [7][8][9] ; la osteotomía a dos niveles (cúbito y radio) 10,11 ; y el uso complementario de fijadores externos 12 .…”
Section: Imagen Problema Discusiónunclassified